A morpho-histological analysis of the exoskeleton of Clathrozoella medeae (Cnidaria, Hydrozoa) reveals insights into the taxonomy of Clathrozoellidae and Hydroidolina - María A. Mendoza-Becerril; Antonio C. Marques (PeerJ)
The taxonomic complexity of the families Clathrozoidae and Clathrozoellidae, rooted in early 20th-century hydroid descriptions, highlights the need for comprehensive and detailed morphological analyses. This study aimed to elucidate the histology of the polypoid stage of Clathrozoella medeae Peña Cantero, Vervoort & Watson, 2003, with a particular emphasis on its exoskeletal structure. Specimens from the National Museum of Natural History were examined histologically using different staining techniques. The results revealed a three-layered mesoglea, diverse gland cells, and an exoskeleton comprising chitin and structural proteins, with notable differences from other anthoathecate hydroids. These results have significant implications for the taxonomy and evolutionary relationships of Clathrozoellidae and Hydroidolina, as they highlight the importance of detailed histological data in understanding the unique exoskeletal architecture of C. medeae, termed “exoskeleton tube”, which distinguishes it from other hydroids, and provide critical insights into the homology and phylogenetic position of Clathrozoellidae.